2022
DOI: 10.1101/2022.08.28.505614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for the Existence of a Bacterial Etiology for Alzheimer’s Disease and for a Temporal-Spatial Development of a Pathogenic Microbiome in the Brain

Abstract: Background: Over the last few decades, a growing body of evidence suggests a role for various infectious agents in Alzheimers Disease (AD) pathogenesis. Despite diverse pathogens (virus, bacteria, or fungi) being detected in AD subjects brains, most research has focused on individual pathogens and only a few studies investigated the hypothesis of a bacterial brain microbiome. We profiled the bacterial communities present in non-demented controls and AD subject' brains. Results: We obtained post-mortem samples… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…Over recent decades multiple studies on post mortem AD brains have reported that diverse pathogens are present, ranging from bacteria to fungi to viruses. [45][46][47][48][49][50][51][52][53] Archaea, Chloroplastida, and Holozoa have also been reported in the brain. 54,55 There are multiple potential routes of entry to the brain (Figure 2).…”
Section: Microbes In the Ad Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent decades multiple studies on post mortem AD brains have reported that diverse pathogens are present, ranging from bacteria to fungi to viruses. [45][46][47][48][49][50][51][52][53] Archaea, Chloroplastida, and Holozoa have also been reported in the brain. 54,55 There are multiple potential routes of entry to the brain (Figure 2).…”
Section: Microbes In the Ad Brainmentioning
confidence: 99%
“…However, two recent studies identified potential differences in the microbiota of AD and age-matched brains. 53,55 One possible explanation is that dementias such as AD can have diverse etiologies in the same way that pneumonia can be caused by a variety of organisms. For example, viruses (influenza, COVID-19, sometimes herpesviruses), bacteria (Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, and others), and fungi (Aspergillus spp., Mucor spp., Candida spp., Cryptococcus spp.)…”
Section: Microbes In the Ad Brainmentioning
confidence: 99%
“…For example, a microbe can be present but asymptomatic: most HSV1-infected individuals do not develop coldsores or other lesions, and many people infected with Mycobacterium tuberculosis do not develop tuberculosis. However, two recent studies identified potential differences in the microbiota of AD and age-matched brains [53,55]. One possible explanation is that dementias such as AD can have diverse etiologies in the same way that pneumonia can be caused by a variety of organisms.…”
Section: Microbes In Ad Brainmentioning
confidence: 99%
“…Diverse methods are available for rDNA amplification, all based on conserved sequences. Ehrlich and colleagues have devised a pandomain assay for specifically amplifying and sequencing rDNAs (16S for prokaryotes; and 18S/23S for eukaryotic microbes) and have demonstrated that the strategy is broadly inclusive, highly sensitive, and species-specific [53,114,124,125]. The general method for 16S pandomain analyses reported by Earl et al was able to accurately characterize highly complex polymicrobial specimens containing hundreds of different species present at molar input levels that vary by more than three orders of magnitude.…”
Section: (Iii) Dna-based Rdna Amplificationmentioning
confidence: 99%
See 1 more Smart Citation